Universal Precautions against HIV and other Blood-Borne Pathogens - Knowledge, Attitude and Compliance among health professionals in Obstetrics and Gynecology - Dhaliwal, Bhalinder; Saha, Pradip Kumar; Goel, Poonam; Huria, Anju (Nepal Journal of Obstetrics and Gynaecology, 2011)
Aim: To assess the knowledge and compliance with universal precautions (UP) for the labour wards, delivery and operating rooms by Doctors, Nurses and Technicians Methods: Study Design: The study was conducted in two teaching hospitals in Chandigarh. Health Care Worker working in the Obstetrics and Gynecology department were surveyed by a pretested detailed confidential questionnaire to asses the knowledge and compliance with UP. And also if they are not using what could be the reason for noncompliance. Results: Hundred percent of doctor had knowledge about UP where as it was 80% in staff nurse and 82% in OT technician. Around Thirty eight percent of the respondent always used double gloves, 18.4% protective eyewear, 34.5% protective outer clothing (plastic inner covering wear inside gown) and 10.5% used Gumshoes (protective foot wear). Around six percent respondent never used double gloves, 64% protective eyes wear, and 13.3% protective outer clothing and 61.2% never used Gumshoes. Reasons for noncompliance with UP as elicited by this study included time constraints (53%), inconvenience (19.3%), non-availability of protective barrier (88%) and presumption that patient was not infected (51.6%). Conclusions: Results from this study reveal that there is a fair level of knowledge about universal precaution among the Health Care Worker (HCW). But Compliance with universal precautions by participant is poor. So, Training programs and other strategy should be put in place to promote the appropriate use universal precaution among Health care professional. Key words: Knowledge, Attitude, Compliance of Universal Precautions DOI: http://dx.doi.org/10.3126/njog.v6i1.5246 NJOG 2011; 6(1): 13-16